Thermal Conductivity of Snow, Firn, and Porous Ice From 3‐D Image‐Based Computations. Issue 22 (16th November 2019) - Calonne, Neige; Milliancourt, Lucas; Burr, Alexis; Philip, Armelle; Martin, Christophe L.; Flin, Frederic; Geindreau, Christian
Abstract: Estimating thermal conductivity of snow, firn, and porous ice is key for modeling the thermal regime of alpine and polar glaciers. Whereas thermal conductivity of snow was widely investigated, studies on firn and porous ice are very scarce. This study presents the effective thermal conductivity tensor computed from 64 3‐D images of microstructures of snow, antarctic firn, and porous ice at −3, −20, and −60°C. We show that, in contrast with snow, conductivity of firn and porous ice correlates linearly with density, is approximately isotropic, and is largely impacted by temperature. We report that performances of commonly used estimates of thermal conductivity vary largely with density. In particular, formulas designed for snow lead to significant underestimations when applied to denser ice structures. We present a new formulation to accurately estimate the thermal conductivity throughout the whole density range, from fresh snow to bubbly ice, and for any temperature conditions encountered in glaciers. Plain Language Summary: Understanding how temperature fluctuations are propagated through snow, firn, and porous ice is crucial for many applications related to alpine and polar glaciers. Whereas thermal conductivity of snow was widely investigated, studies on firn and porous ice are very scarce. This study provides the effective thermal conductivities computed from 64 3‐D images of microstructures of snow, antarctic firn, and porous ice at temperatures of −3, −20, and −60°C. For the first time, the evolution of thermal conductivity over the full range of density is revealed, from fresh snow, with up to 80% of air, to bubbly ice, with less than 10% of air. We show that, in contrast with snow, thermal conductivity of firn and porous ice correlates linearly with density, is approximately isotropic, and is largely impacted by temperature. Assessing some commonly used predictive formulas of thermal conductivity of snow, firn, and porous ice, we found that none allowed for robust estimations throughout the full density range. In particular, formulas designed for snow lead to significant underestimations when applied to denser ice structures. We present a new density‐ and temperature‐based formula to accurately estimate thermal conductivity of snow, firn, and porous ice in alpine or polar conditions. Key Points: Snow‐designed predictive formulas significantly underestimate the thermal conductivity when applied to firn and porous ice Thermal conductivity of firn and porous ice is isotropic and linearly correlated to density We present a new formula for the thermal conductivity of snow, firn, and porous ice based on density and temperature